Kaplan & Sadock's pocket handbook of psychiatric drug treatment - Sadock, Benjamin J. , 1933-; Sadock, Virginia A.; Sussman, Norman (Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"This is the fifth edition of Kaplan and Sadock's Pocket Handbook of Psychiatric Drug Treatment, which covers the entire spectrum of drug therapy as used in the everyday practice of psychiatry. Nonpsychiatric physicians, especially primary care specialists who prescribe psychotropic medications, will also find this book valuable. Other mental health professionals, including nurses, psychologists, and social workers, can use the book to provide them with information about the psychiatric drugs prescribed for their patients or clients"--Provided by publisher